Acute Renal Failure and Seizure following Multiple Wasp Stings: A Case Report - Kumar, MK; Thakur, SN (Journal of Nepal Paediatric Society, 2012)
Wasps and bees descend from order Hymenoptera. All social wasps belong to family Vespidae. Their stings are not usually life threatening, causing mainly local reactions and rarely anaphylaxis and serious systemic manifestations. Though a few stings cause no major problems, multiple stings can cause serious effects like massive hemolysis, acute renal failure, encephalopathy, multiorgan dysfunction. We report a six years boy with acute renal failure and seizure following multiple wasp stings. Key words: Multiple wasp stings; Acute renal failure; Hymenoptera DOI: http://dx.doi.org/10.3126/jnps.v32i1.5238 J. Nepal Paediatr. Soc. Vol.32(1) 2012 65-68